Systematics of the Satyrium (Superflua) deria (Moore, 1865) species group with description of a new species from Afghanistan (Lepidoptera, Lycaenidae) - Krupitsky, Anatoly V.; Pljushtch, Igor G.; Pak, Oleg V. (Zootaxa, 2018)
Satyrium (Superflua) deria (Moore, 1865) species group is revised. The group contains four species: S. (S.) deria (northern Himalayan region and southwestern Pamirs), S. (S.) muksuria Churkin & Pletnev, 2010 (southwestern Alay Mountains and Peter the Great Range), S. (S.) zabirovi Churkin & Pletnev, 2010 (from northwestern Pamirs to Darvaz Range), and S. (S.) hazarajatica sp. n. (type locality: central Afghanistan, Bamyan Province, Band-e Amir valley, env. Yakawlang). The new species differs from the other members of the group in the male and female genitalia, wing pattern, and colouration. Female genitalia of the S. (S.) deria, S. (S.) muksuria and S. (S.) zabirovi are illustrated and discussed for the first time. S. (S.) muksuria is newly recorded from the Alay Mountains. A key to species of the S. (S.) deria group is provided.